Technological advances, human performance, and the operation of nuclear facilities - Corrado, Jonathan K., author; Sega, Ronald M., advisor; Bradley, Thomas H., committee member; Chong, Edwin K. P., committee member; Young, Peter M., committee member (Colorado State University. Libraries, 2017)
Many unfortunate and unintended adverse industrial incidents occur across the United States each year, and the nuclear industry is no exception. Depending on their severity, these incidents can be problematic for people, the facilities, and surrounding environments. Human error is a contributing factor in many such incidents. This dissertation first explored the hypothesis that technological changes that affect how operators interact within the systems of the nuclear facilities exacerbate the cost of incidents caused by human error. I conducted a review of nuclear incidents in the United States from 1955 through 2010 that reached Level 3 (serious incident) or higher on the International Nuclear Events Scale (INES). The cost of each incident at facilities that had recently undergone technological changes affecting plant operators' jobs was compared to the cost of events at facilities that had not undergone changes. A t-test determined a statistically significant difference between the two groups, confirming the hypothesis. Next, I conducted a follow-on study to determine the impact of the incorporation of new technologies into nuclear facilities. The data indicated that spending more money on upgrades increased the facility's capacity as well as the number of incidents reported, but the incident severity was minor. Finally, I discuss the impact of human error on plant operations and the impact of evolving technology on the 21st-century operator, proposing a methodology to overcome these challenges by applying the systems engineering process.
Keywords: human factors; nuclear operation; human error; technology advances; human performance